Does the concept of residential college offset the effects of socioeconomic status on university students' academic performance? - Gui, Ping Ping; Alam, Gazi Mahabubul; Hassan, Aminuddin (Emerald Publishing, 2023)
Purpose: This comparative study aims to examine the role of Socio-Economic Status (SES) on the academic performance of university students who hold both the status of Residential College (RC) and non-RC. The study further investigates whether the RC is able to offset the effects of SES on students' learning performance to ensure education equity and inclusion in China. Design/methodology/approach: Data are collected through a questionnaire given to RC and non-RC students enrolled in three public universities in China. A quasi-experimental design is implemented to investigate the potential correlation, if any, between SES, RC and academic performance. Findings: The results reveal that SES influences academic performance of RC students. Furthermore, the findings strongly suggest that RCs negatively moderate the effect of SES on academic performance. Research limitations/implications: This study examines RCs within a specific type of university in China, which may limit the generalizability of findings. Additionally, it uses a quasi-experimental method and relies solely on quantitative data, which may also introduce limitations. Practical implications: Provided in this study is evidence that RCs can be an innovative way to bolster inclusive and equitable quality education for students from diverse backgrounds in China. Originality/value: This study enriches the existing literature by exploring the relationships between RC, SES and academic performance in China. In addition, it provides significant references to whether RC can fulfill students' education equity and inclusion.